Accounting for labor demand effects in structural labor supply models - Andreas Peichl; Sebastian Siegloch (Institute for the Study of Labor (IZA), 2010)
When assessing the effects of policy reforms on the labor market, most studies only focus on labor supply. The interaction of supply and demand side is not explicitly modeled, which might lead to biased estimates of potential labor market outcomes. This paper proposes a straightforward method to remedy this shortcoming. We use information on firms' labor demand behavior and feed them into a structural labor supply model, completing the partial analysis of the labor market on the microdata level. We show the performance and relevance of our extension by introducing a pure labor supply side reform, the workfare concept, in Germany and simulating the labor market outcome of the reform. We find that demand effects offset about 25 percent of the positive labor supply effect of the policy reform.
Keywords: J22; J23; J68; 330; labor supply; labor demand; policy reform; workfare